2010
DOI: 10.1159/000313876
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Endothelial Cell Responses in vitro and in vivo: Modulation by Zoledronic Acid and Paclitaxel?

Abstract: Background/Aims: The cytotoxic agent paclitaxel and the anti-resorptive drug zoledronic acid are used in the early and advanced breast cancer setting, respectively. Both agents have been demonstrated to have anti-tumour and anti-endothelial actions. Combining paclitaxel with zoledronic acid induces a synergistic increase in apoptotic breast cancer cell death in vitro, suggesting an increased anti-tumour effect in vivo, but any specific effects on the normal microvasculature and potential side-effects of this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 72 publications
3
31
0
Order By: Relevance
“…Detection of increased levels of unprenylated Rap1A is a surrogate measurement of NBP uptake by cells in vitro and of inhibition of prenylation (2931). To confirm that the inhibition of angiogenesis occurs through the effect of ZA, we measured the levels of unprenylated Rap1A by western blot.…”
Section: Resultsmentioning
confidence: 99%
“…Detection of increased levels of unprenylated Rap1A is a surrogate measurement of NBP uptake by cells in vitro and of inhibition of prenylation (2931). To confirm that the inhibition of angiogenesis occurs through the effect of ZA, we measured the levels of unprenylated Rap1A by western blot.…”
Section: Resultsmentioning
confidence: 99%
“…Detection of increased levels of unprenylated Rap1A is a common surrogate measurement of NBP uptake by cells in vitro and inhibition of the mevalonate pathway (2527). The level of unprenylated Rap1A in PSCs increased as Pam concentration increased (by 137.8% at 0.1 μM to 297.5% at 10 μM compared with untreated cells) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The strong modulation of integrin CD49d may indicate a possible effect of zoledronic acid on cell anchorage [34]. Several studies have shown that zoledronic acid induces antiangiogenic responses, with reduced human dermal microvascular endothelial cell proliferation, accumulation of cells in S phase, and inhibition of migration, tube formation and Rap1a prenylation [35]. To determine the functional cellular responses to adhesion-blocking antibodies and zoledronic acid, a cell migration assay was performed, where the PC3 cells adhered to and migrated through a monolayer of BME cells.…”
Section: Discussionmentioning
confidence: 99%